Poro Point Special Economic and Freeport Zone Development Framework Planning Project final report (UP PLANADES, 2003)
Shows the strategic framework/structure plan for the western section of the Poro Point Special Economic and Freeport Zone (PPSEFZ) to guide succeeding detailed planning by developers.